Modulation of Tumor Immunity by Soluble and Membrane-Bound Molecules at the Immunological Synapse - Pablo A. González; Leandro J. Carreño; Pablo F. Céspedes; Susan M. Bueno; Claudia A. Riedel; Alexis M. Kalergis (Clinical and Developmental Immunology)
To circumvent pathology caused by infectious microbes and tumor growth, the host immune system must constantly clear harmful microorganisms and potentially malignant transformed cells. This task is accomplished in part by T-cells, which can directly kill infected or tumorigenic cells. A crucial event determining the recognition and elimination of detrimental cells is antigen recognition by the T cell receptor (TCR) expressed on the surface of T cells. Upon binding of the TCR to cognate peptide-MHC complexes presented on the surface of antigen presenting cells (APCs), a specialized supramolecular structure known as the immunological synapse (IS) assembles at the T cell-APC interface. Such a structure involves massive redistribution of membrane proteins, including TCR/pMHC complexes, modulatory receptor pairs, and adhesion molecules. Furthermore, assembly of the immunological synapse leads to intracellular events that modulate and define the magnitude and characteristics of the T cell response. Here, we discuss recent literature on the regulation and assembly of IS and the mechanisms evolved by tumors to modulate its function to escape T cell cytotoxicity, as well as novel strategies targeting the IS for therapy.